Stock Market Crashes in Australia: A Brief Technical Note - John Christie (Australasian Accounting, Business and Finance Journal, 2021)
This paper analyses the three stock market crashes in Australia which have occurred since the All Ordinaries Index was established in 1980. The index behaves in an approximately exponential manner leading up to each market crash and this behaviour can be interpreted as a sign of a looming market crash.
Keywords: Stock Market Crashes; Australia